Dielectric and ferroelectric characteristics of barium zirconate titanate ceramics prepared from mixed oxide method - Moura, F. [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Stojanovic, B. D. [UNESP]; Zaghete, M. A. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V. Sa, 2008)
Barium zirconium titanate (BZT) ceramics were prepared by mixed oxide method. X-ray diffraction showed the presence of a single phase while Raman scattering confirmed structural transitions as a function of different Zr/Ti ratio. The addition of Zr strongly influenced the crystal structure and electrical properties of the ceramics. A typical hysteresis loops were observed for all investigated compositions. BZT ceramics with 15 mol% Zr have shown a ferroelectric to paraelectric transition at around 77 degrees C. (C) 2007 Published by Elsevier B.V.
Keywords: ferroelectrics; x-ray diffraction; dielectric response